3D-printed heart model to guide LAA closure: useful in clinical practice? - Hachulla, Anne-Lise; Noble, Stéphane; Guglielmi, Gabriel; Agulleiro, Daniel; Müller, Hajo; Vallée, Jean-Paul (European Radiology, 2019)
Objectives: Correct device sizing for left atrial appendage (LAA) closure remains challenging due to complex LAA shapes. The aim of our study was to investigative the utility of personalized 3D-printed models (P3DPM) of the LAA to guide device size selection.Methods: Fifteen patients (75.4 ±8.5years) scheduled for LAA closure using an Amulet device underwent cardiac computed tomography (CT). The LAA was segmented by semiautomatic algorithms using Vitrea® software. A 1.5-mm LAA thick shell was exported in stereolithography format and printed using TangoPlus flexible material. Different Amulet device sizes on the P3DPM were tested. New P3DPM-CT with the device was acquired in order to appreciate the proximal disc sealing the LAA ostium and the compression of the distal lobe within the LAA. We predicted the device size with P3DPM and compared this with the device sizes predicted by transesophageal echocardiography (TEE) and CT as well as the device size implanted in patients.Results: The device size predicted by 3D-TEE and CT corresponded to the implanted device size in 8/15 (53%) and 10/15 (67%), respectively. The predicted device size from the P3DPM was accurate in all patients, obtaining perfect contact with the LAA wall, without device instability or excessive compression. P3DPM-CT with the deployed device showed device deformation and positioning of the disk in relation to the pulmonary veins, allowing us to determine the best device size in all 15 cases.Conclusion: P3DPM allowed us to simulate the LAA closure procedure and thus helped to identify the best Amulet size and position within the LAA.Key Points: • A 3D-printed heart model allows to simulate the LAA closure procedure. • A 3D-printed heart model allowed to identify the optimal Amulet size and position. • 3D-printed heart models may contribute to reduce the Amulet implantation learning curve.